Pelatihan Digital Marketing menggunakan Facebook Ads dan Marketplace Shopee sebagai strategi peningkatan Penjualan Pada UMKM Madu Mayeesha - nurhadi; Pareza Alam Jusia; Ronald Naibaho; Khairuldi; Eko Arip Winanto; Dodi Sandra; Beni Irawan; Suwanto (Jurnal Pengabdian Masyarakat UNAMA, 2023)
The community service activities carried out are community service activities funded by the Jambi Dinamika Bangsa Foundation. The implementation of this activity is carried out in the form of practicum and discussion to train training participants, namely Madu Mayeesha UMKM actors in terms of graphic design and Facebook Ads and Shopee Marketplace, to increase sales through digital marketing. This training uses the following methods: problem formulation stage, solution determination stage, settlement method, evaluation stage, and output. This training utilizes Graphic Design software such as: CorelDraw, Photoshop and Canva to create promotional designs or advertising materials for mayeesha honey products